Investigation Readiness of teachers and students in online learning: A Study Quantitative method - Mappalotteng, Abdul Muis; H., Nurhikmah; Wijaya, Hengki; Weismann, Ivan Th. J.; Nur, Istar Al Fatih Malik (Journal of Applied Science, Engineering, Technology, and Education, 2025)
Online learning has become a reality in Indonesia in mid-2022. Conventional learning has experienced a suspended animation, and suddenly, online learning has become viral and a necessity for all schools, including high schools. This study aims to determine the relationship between teacher readiness and high school student’s readiness for online learning during the post pandemic. There were 407 teacher and high school student respondents, respectively. They used the correlation approach, F test, and regression equation to measure the correlation between each teacher's readiness and student readiness indicator. The findings show that the relationship between teacher and student readiness is insignificant. Readiness of online learning infrastructure has more influence than indicators of digital literacy and teacher self-efficacy, pedagogical abilities, teacher attitudes, and readiness for document management. The teacher’s attitude toward online learning does not influence student readiness for online learning.